2023
DOI: 10.1128/jvi.01596-22
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Spike Receptor Binding Domain Class V Cryptic Epitope by an Antibody with Pan-Sarbecovirus Activity

Abstract: Characterization of MAbs against SARS-CoV-2, elicited through vaccination or natural infection, has provided vital immunotherapeutic options for curbing the COVID-19 pandemic and has supplied critical insights into SARS-CoV-2 escape, transmissibility, and mechanisms of viral inactivation. Neutralizing MAbs that target the RBD but do not block ACE2 binding are of particular interest because the epitopes are well conserved within sarbecoviruses and MAbs targeting this area demonstrate cross-reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…Previously, we have described a set of RBD neutralizing antibodies (WRAIR-2057, WRAIR-2063, and WRAIR-2134) isolated from a convalescent human subject which were of particular interest because of their novel epitope on the SARS-CoV-2 RBD 34 , 54 . Our binding competition and alanine scanning experiments indicated that WRAIR-5001 also targets a similar epitope (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have described a set of RBD neutralizing antibodies (WRAIR-2057, WRAIR-2063, and WRAIR-2134) isolated from a convalescent human subject which were of particular interest because of their novel epitope on the SARS-CoV-2 RBD 34 , 54 . Our binding competition and alanine scanning experiments indicated that WRAIR-5001 also targets a similar epitope (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the clinical application of anti-RBD antibodies has led to reduced neutralization and inhibitory activities. 22 , 26 , 30 , 31 , 58 Although efforts to develop broadly neutralizing antibodies that target pan-coronavirus conserved epitopes are actively underway, 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 the possibility of emerging immune-evading mutant variants remains, posing a recurrent challenge to monoclonal antibody therapy. Therefore, the exploration of alternative approaches is attractive.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that despite the rapid evolution of the SARS-CoV-2 virus, this region is highly conserved, suggesting that the design of glycan modifications should avoid targeting these highly conserved regions. Interestingly, antibodies targeting this epitope demonstrate moderate neutralizing potency with cross-reactivity within sarbecoviruses ( 54 ). Additionally, in a separate study, the introduction of glycans at non-conserved sites within the core antigenic sequence of sarbecovirus RBD effectively enhanced the presentation of conserved epitopes to the immune system.…”
Section: Discussionmentioning
confidence: 99%